Can fluoxetine mitigate mental health decline in musculoskeletal trauma patients: a pilot single-center randomized clinical trial - Elizabeth Lossada-Soto; Marissa Pazik; Mary Beth Horodyski; Terrie Vasilopoulos; Ludmila Barbosa de Faria; Carol Mathews; Jennifer Hagen (Pilot and Feasibility Studies, 2022)
Abstract Background Musculoskeletal trauma is one of the leading causes of disability in the USA and its negative quality of life impact extends beyond that of physical recovery. More than 50% of victims of musculoskeletal trauma suffer lasting mental health issues and post-traumatic stress disorder (PTSD) symptomology following their injury. These symptoms can develop across all spectrums of patients and are independent predictors of poor outcome. Access to mental health care is limited, expensive, and time intensive, and a large majority of the trauma population do not get to utilize this valuable resource. This leaves the burden of management on the orthopedic team, as they are often the only point of contact for the patient within the medical system. Methods This is a single-center, repeated measures, randomized controlled pilot study including up to 100 orthopedic trauma patients aged between 18 and 85 years of age. Subjects are approached during their index hospitalization and are randomized to one of two pharmaceutical interventions, fluoxetine (also known as Prozac) or calcium, for 9 months. Fluoxetine is a selective serotonin reuptake inhibitor (SSRI) that is supported for the treatment of PTSD by the American Psychiatric Association. It is low-cost and has minimal side effects and withdrawal symptoms if stopped suddenly. Calcium is a supplement with minimal side effects that is used in our study for its bone-healing potential. Feasibility will be indexed by recruitment feasibility, randomization feasibility, medical adherence, anti-depressant side effects, and fracture union rate. Subjects will complete physical and mental health surveys at baseline, 2 weeks, 6 weeks, 3 months, 6 months, and 1 year. Discussion The goals of this exploratory clinical trial are to: develop a safe, feasible, and time-limited protocol effect of immediate (post-injury) treatment with fluoxetine for use by orthopedic providers and other non-mental health care providers treating victims of musculoskeletal trauma (Aim 1), and test the for preliminary effects of the protocol on development of PTSD symptomology and physical recovery in these patients (Aim 2). This study is novel in that it strives to prevent the development of symptomology from the time of injury and empowers surgeons to manage their patients in a more holistic manner. Trial registration ClinicalTrials.gov, NCT04850222 . Registered on April 20, 2021.